The use of scanning acoustic microscope for flaw detection in metallic materials - Idris, Jamaliah; Teoh, T. L. (Faculty of Mechanical Engineering, 1998)
The main objective of this paper is to understand the principles and theories behind the operation of the equipment, and its architecture. The advantages and limitations of the scanning a coustic microscope are also investigated by imaging a set of samples. The principle of operation of a scanning acoustic microscope is producing magnified acoustic images of the surface or interior of a solid by passing high-frequency focused acoustic pulses through the material and displaying the received signal in the image form as shades of grey. The significant advantage to be gained in using scanning acoustic microscope for producing images are the ability of acoustic waves to penetrate opaque material and the distinctive origin of contrast in the mechanical properties of the specimen. Three sets of samples are observed under the scanning acoustic microscope and they are Vickers hardness indention samples, quenched samples and porosity samples. It is found that results obtained for the samples are subjected to the overall ability of the equipment used. The operating frequency was one of the most significant limiting factors in this work, as the resolution obtained was not as high as would be favourable. However, satisfactory images with distinctive contrast were still achieved. One of the advantages of using scanning acoustic microscope, which is the sub-surface imaging ability, is also revealed. Finally, the operating software of the equipment is also an important aspect that should be given proper consideration.